النشاط البدني الرياضي و العولمة - سليماني، نورالدين (Mohamed Boudiaf University of M'Sila, 2022)
الملخص : المطبوعة موجهة لطلبة السنة الثانية ليسانس قسم التربية البدنية بمعهد علوم وتقنيات النشاطات البدنية والرياضية بجامعة المسيلة حيث تناولت المطبوعة في البداية لمدخل مفاهيمي للعولمة ثم تطرقنا الى مظاهر العولمة و اثارها ثم مفاهيم النشاط البدني الرياضي و ظاهرة العولمة و و العوامل المشتركة بين النشاط البدني الرياضي و و العولمة واقتصاد السوق الحرة و في الأخير تطرقنا الى اهداف الممارسة الرياضية الترفيهية و الترويحية في النظام التنافسي. Abstract : The publication is directed to the second year students of the Bachelor of Physical Education Department at the Institute of Sciences and Techniques of Physical and Sports Activities at the University of M'sila. The publication initially dealt with a conceptual introduction to globalization, then we addressed the manifestations of globalization and its effects, then the concepts of physical sports activity and the phenomenon of globalization and the common factors between physical sports activity and globalization and the free market economy. Finally, we addressed the objectives of recreational and leisure sports practice in the competitive system.
Keywords: التربية البدنية; العولمة; الممارسة الرياضية الترفيهية و الترويحية